2022
DOI: 10.3390/jpm12071142
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of NAFLD in Adults with Glomerular Hyperfiltration: An 8-Year Cohort Study Based on 147,162 Koreans

Abstract: This study evaluated whether glomerular hyperfiltration (GHF) could predict nonalcoholic fatty liver disease (NAFLD) and fibrosis. A longitudinal cohort study including 147,479 participants aged 20–65 years without NAFLD and kidney disease at baseline was performed. GHF cutoff values were defined as age- and sex-specific estimated glomerular filtration rate (eGFRs) above the 95th percentile, and eGFR values between the 50th and 65th percentiles were used as reference groups. NAFLD was diagnosed via abdominal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Another recent study conducted on a large cohort of Spanish patients with prediabetes and visceral adiposity showed an independent association between liver steatosis and GH, and the age-mediated GFR reduction appears to be potentiated by MASLD [22]. Finally, a study conducted In an Asiatic population of 147,162 Korean subjects without CKD nor hepatic steatosis and followed up for 4 years showed that the presence of GH at baseline (present in 5% of the cohort) was an independent risk factor for the development of liver fat diagnosed by US (OR 1.21, CI 95% 1.14-1.29) and for its progression to fibrosis assessed by the NAFLD fibrosis score (OR 1.42, CI 95% 1.11-1.82) [23]. In addition, the persistence of GH over time further increased this risk up to 13%.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study conducted on a large cohort of Spanish patients with prediabetes and visceral adiposity showed an independent association between liver steatosis and GH, and the age-mediated GFR reduction appears to be potentiated by MASLD [22]. Finally, a study conducted In an Asiatic population of 147,162 Korean subjects without CKD nor hepatic steatosis and followed up for 4 years showed that the presence of GH at baseline (present in 5% of the cohort) was an independent risk factor for the development of liver fat diagnosed by US (OR 1.21, CI 95% 1.14-1.29) and for its progression to fibrosis assessed by the NAFLD fibrosis score (OR 1.42, CI 95% 1.11-1.82) [23]. In addition, the persistence of GH over time further increased this risk up to 13%.…”
Section: Discussionmentioning
confidence: 99%
“…We also reported a study about the simple self-assessment score consists of age, sex, waist circumference, BMI, history of T2DM and dyslipidemia, alcohol intake, physical activity, and menopause status, which are independently associated with NAFLD, and this simple score could be a guide to identify individuals at high-risk of NAFLD [84]. And we studied the association between glomerular hyperfiltration (GHF) and the risk of NAFLD [85]. In a longitudinal study including 147,479 relatively healthy adults, we found that GHF (defined as age-and sex-specific estimated glomerular filtration rate above the 95th percentile) status was associated with future NAFLD development assessed using ultrasonography (US) and progression to fibrosis assessed using NAFLD fibrosis score and FIB-4.…”
Section: Characteristics Of Nafld In Koreansmentioning
confidence: 99%
“…11 On the other hand, glomerular hyperfiltration is associated with an increased risk of NAFLD and liver fibrosis even in healthy adults. 12 In early 2020, the term NAFLD was replaced by the term "metabolic dysfunction-associated fatty liver disease" (MAFLD) to better highlight the contribution of systemic metabolic dysregulation in the pathogenesis of NAFLD, beyond its histopathological similarities to alcohol-related liver disease. 13 Indeed, MAFLD is a diseaseentity that-unlike NAFLD-in addition to fatty liver disorders, encompasses at least one of the following three criteria: overweight/ obesity, T2DM, or two or more metabolic dysregulations in lean/ normal weight subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in children and adults with the metabolic syndrome, NAFLD is associated with glomerular hyperfiltration, 7,8 which is a well‐established pathogenic factor for accelerated renal function loss in subjects with obesity, diabetes and/or CKD, 9,10 and predicts all‐cause mortality even in apparently healthy populations 11 . On the other hand, glomerular hyperfiltration is associated with an increased risk of NAFLD and liver fibrosis even in healthy adults 12 …”
Section: Introductionmentioning
confidence: 99%